LEGAL REGULATION OF LABOUR RELATIONS IN UKRAINE UNDER CONDITIONS OF MARTIAL LAW: A REVIEW OF CHANGES - Kmetyk, Khrystina; Shiyan, Yulia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to define the main changes that have taken place in legal regulation of labour relations under the legal regime of martial law in Ukraine. Research methods: the methods of comparative and documentary analysis, documentary synthesis and generalization and the cognitive-analytical method are used. Results: the authors characterize the main changes in legal regulation of labour relations during the period of martial law in Ukraine. In addition, the author emphasises the urgent need to study the impact of martial law on labour relations in Ukraine, as well as to adapt labour legislation to the new conditions of today. Discussion: the provisions of the Law of Ukraine “On Organization of Labour Relations under the Conditions of Martial Law” N 2136-IX dated March 15, 2022, which at present occupies a key position in the sphere of regulation of labour relation were reviewed and analysed.